Type II codes over F2m + uF2m - Nemenzo, Fidel R. (2013)
We look at the special class of self-dual codes called Type II codes over the alphabet Rm =F2m + uF2m where u2 = 0. Properties of the Gray maps which take self-dual codes over Rm to self-dual codes over the subrings F2m and Rr = F2r + uF2r for divisors r of m are studied. We give a mass formula for Type II codes over Rm and classify such codes of length n⩽8 for m=2,3,4,5,6 and 7.